Haunting of Winchester House Ghost stories - Latt, David Michael, 1966-; Prendes, Jose.; Atkins, Mark.; Kellerman, Lisa.; Holms, Michael; Boykin, Tomas; Ridenhour, Chris; Asylum (Firm); Echo Bridge Home Entertainment ([S.l.] : Echo Bridge Home Entertainment, 2010)
Haunting of Winchester House: A family moves into the mansion to act as caretakers, but when a malevolent force abducts their daughter they discover why the house deserves its reputation as one of the most haunted places in America.
Ghost stories: Eight tales of terror as seen on the FOX Family Channel: Heartsick -- From the ashes -- Winner takes all -- The inheritance -- Denial -- Erased -- Parting shot -- Consumers.
Blu-Ray requires Blu-Ray player.
"Unrated uncut version"--Container.
Haunting of Winchester House: Director of photography, Mark Atkins ; edited by Marq Morrison ; music composed by Chris Ridenhour.
Ghost stories: Narrated by Rip Torn ; Directed by Jeffery Fine, Greg Francis, Stuart Taylor, Frank Wayne and more.
Haunting of Winchester House: Lisa Kellerman, Michael Holms, Tomas Boykin.
Ghost stories: Juliette Dunn, louis Lu, christina Chang, Kimberly Kay, Richard Kinter, Cynthis Henderson, Burnadair Hunt, Christopher Mattox, Greg O'Donovan, Maya Israel, Christan Borle.
Keywords: Haunted houses -- Drama; Horror films; Horror tales